2001
DOI: 10.1097/00005131-200109000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Control of Severe Hemorrhage Using C-Clamp and Pelvic Packing in Multiply Injured Patients With Pelvic Ring Disruption

Abstract: Sequential measurements of blood lactate levels during the early period after injury may provide a more rapid and reliable estimation of true severity of hemorrhage than routinely used parameters. Pelvic packing in addition to pelvic ring fixation with a C-clamp allows for effective control of severe hemorrhage in multiply injured patients with pelvic ring disruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
1
9

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 267 publications
(110 citation statements)
references
References 25 publications
4
96
1
9
Order By: Relevance
“…Additionally, the ability to clear lactate to normal levels can be used to evaluate the effectiveness of resuscitation. We have previously reported that lactate levels correlate with the outcome of severely injured patients with pelvic fractures [48] and advocate to use this parameter for assessment of the patients hemodynamic state and to monitor success of shock treatment. Definitive "staged" surgical procedures The results of this study confirm previous investigations that rapid localization and control of the major source of hemorrhage is pivotal for survival of multiple injured patients with pelvic ring disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the ability to clear lactate to normal levels can be used to evaluate the effectiveness of resuscitation. We have previously reported that lactate levels correlate with the outcome of severely injured patients with pelvic fractures [48] and advocate to use this parameter for assessment of the patients hemodynamic state and to monitor success of shock treatment. Definitive "staged" surgical procedures The results of this study confirm previous investigations that rapid localization and control of the major source of hemorrhage is pivotal for survival of multiple injured patients with pelvic ring disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical packing of the small pelvis for the treatment of ongoing bleeding can only be successful when pelvic external fixation is carried out beforehand. External fixation and C-clamping create mechanical stability; the fixed bony structures form a resistance to which packing is effective [39]. Contrary to the pelvic binder and C-clamp, the external fixator can remain longer on the pelvic ring.…”
Section: External Fixationmentioning
confidence: 99%
“…Die intensivierte Schocktherapie und ggf. Gerinnungssubstitution wird während der Notfallstabilisierung ununterbrochen weitergeführt [1,2,9,11,22,23] (. Abb.…”
Section: "Becken-notfall"unclassified